A Review on Community-Based Knowledge Transfer and Exchange (KTE) Initiatives for Promoting Well-Being in Older Adults. Issue 4 (4th July 2017) - Syed, M. Anum; Moorhouse, Aynsley; McDonald, Lynn; Hitzig, Sander L.
ABSTRACT: Knowledge transfer and exchange (KTE) processes can facilitate evidence-informed community-based care for seniors, but understanding effective KTE in gerontology is limited. A scoping review was conducted to evaluate the current state of KTE in the community-based sector for seniors. Twelve articles met the inclusion criteria, which addressed a broad variety of topics including caregiving, elder abuse, falls prevention, home-rehabilitation, hospice and dementia care. Studies evaluated KTE practices ( n = 8), developed a KTE intervention ( n = 3), or explored research uptake ( n = 1). Community-based initiatives for seniors informed by KTE processes are scarce, requiring further efforts at the research, practice and policy levels.